Mixed neuropathologies and associations with domain-specific cognitive decline. (24th October 2017) - Brenowitz, Willa D.; Hubbard, Rebecca A.; Keene, C. Dirk; Hawes, Stephen E.; Longstreth, W.T.; Woltjer, Randy L.; Kukull, Walter A.
Abstract : Objective: To test whether decline in specific cognitive domains associated with Alzheimer disease neuropathologic change (ADNC) is modified by co-occurrence of other neuropathologies such as Lewy body disease (LBD) or vascular brain injury (VBI). Methods: Data came from 1, 603 autopsied participants evaluated at US Alzheimer's Disease Centers. Standardized z scores in memory, attention, language, and executive function were derived from neuropsychological test scores assessed at each annual visit. Multivariable linear mixed-effects models assessed associations between neuropathologies and longitudinal trajectories of domain scores. Results: Compared to other participants, those with ADNC + LBD generally had worse cognitive trajectories, particularly lower initial executive function and faster attention decline. Participants with ADNC + VBI typically had less impairment and slower decline. Interactions were significant between LBD and ADNC for memory ( p = 0.046) and between VBI and ADNC for language ( p = 0.03); decline was slower than expected if these neuropathologies acted additively on the rate of decline. In secondary models, these interactions were limited to those with high ADNC (but not intermediate ADNC). In a subset of 260 participants with data on microinfarct location, cortical and subcortical microinfarcts were associated with decline in memory, language, and executive function in those without ADNC, but this effect was reduced among those with ADNC. Conclusions: ADNC + LBD (but not ADNC + VBI) was associated with poorer executive function and attention compared to other pathology groupings. However, the effect of co-occurring pathologies on cognitive trajectories may depend on the severity of ADNC. Future studies using antemortem biomarkers should seek to replicate these neuropathologic observations.